The larva of Hydropsyche perseus Malicky 2001, endemic to Kerkyra (Corfu) Island, including a key for the known Hydropsyche larvae of the Greek islands - Karaouzas, Ioannis; Kapakos, Yiannis (Zootaxa, 2018)
The larva of Hydropsyche perseus Malicky 2001, endemic species of Kerkyra Island (Corfu), Greece, is described for the first time. The diagnostic features of the species are described and illustrated, and some information regarding its ecology is included. In addition, a tabular key for larvae of the known Hydropsyche species of the Greek Islands is provided.